Lifestyle Creep in the Perspective of Hadith on the Command of Modest Living - Nisa, Nabila Khairun; Uswatun Hasanah; Almunadi (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract This study discusses lifestyle creep from the perspective of hadith on the command of modest living. Lifestyle creep refers to a person's tendency to elevate their lifestyle as their income increases. Although this may seem reasonable in a social and economic context, if left unchecked, it can lead to excessive consumerism and a departure from the principles of modest living taught in Islam. This study aims to provide an understanding of hadith by addressing the modern challenge of lifestyle creep and guiding Muslims to maintain modest living amidst the rapid changes of the times. This study employs a qualitative library research method and adopts the ma’anil hadith approach. This research indicates that hadith encourages a modest lifestyle as an expression of gratitude, humility, self-restraint, and wisdom in managing wealth. Therefore, an extravagant lifestyle marked by lifestyle creep is inconsistent with the values contained in the hadith and is not encouraged in Islam. The command to dress modestly in hadith is also intended to cultivate gratitude for Allah's blessings and promote social tolerance. Keywords: Hadith; Lifestyle Creep; Modest